Moderasi Islam dalam Hadis Jihad: Analisis Teks, Konteks, dan Implementasi Kontemporer - Khoirul, Khoirul; Akino, Sahrijal (SHAHIH (Jurnal Ilmu Kewahyuan), 2025)
The hadith “I am commanded to fight people until they testify...” is among the most frequently misinterpreted texts by certain extremist groups. A purely textual interpretation—divorced from its historical context—has led to a distorted understanding of jihad, which in reality is rich with spiritual, ethical, and social values. This study aims to analyze the meaning of Islamic moderation in relation to this hadith through a textual, contextual, and contemporary implementation approach. The main method employed is a qualitative library research based on classical hadith compilations and relevant secondary sources. The findings reveal that a moderate interpretation of jihad aligns with the objectives of Islamic law (maqāṣid al-sharī‘ah), particularly the protection of life, religion, and societal peace. The hadith in question does not serve as a blanket justification for violence, but rather reflects the prophetic mission of protection and guidance within a specific historical context. Therefore, a comprehensive and contextual understanding is essential to correct the misinterpretation and affirm Islam as a religion of mercy for all creation.